A Few Methods of Solving Optimal Control Problem in Hamilton-Jacobi-Bellman Equation Form - Khadka, Bhimsen; K.C., Durga Jang (Journal of Science and Engineering, 2021)
Non-linear optimal control problem arises in many different areas, for example, engineering, medical sciences, economics, industries, etc. The solution of Hamilton-Jacobi-Bellman equation is connected with the non -linear optimal control problem. In this paper, we formulate the Hamilton-Jacobi-Bellman equation using nonlinear optimal control problem. We also discuss its solutions using Adomian decomposition method, Laplace transform-Homotopy perturbation method and variational iteration method.